The Effect of The Berlitz Method Towards Students’ Vocabulary Mastery at The Eighth Grade of Junior High School Berdikari Lebak Banten in Academic Year 2023/2024 - Nurlatifah, Ade; Sudirman, Ade; Novari, Ari Fajria (Journal of English Education Studies, 2023)
This research aims to determine the significant effect of Berlitz Method towards Students' Vocabulary Mastery at the eighth Grade of Junior High School Berdikari Cijaku Lebak Banten in academic year 2023/2024. This research used a quantitative approach and quasi-experimental design. This research used two classes, namely the control class and the experimental class. The sample collecting technique is cluster random sampling. The researcher used class VII A (20 students) as the experimental class and class VII B (20 students) as the control class. The experimental class was taught using the Berlitz Method, while the control group was taught using Talking sticks. In the data collection technique, the researcher gave a pre-test and post-test. In analyzing the data, the researcher used SPSS 25 statistical calculations and post-test results of control and experimental classes to analyze hypothesis testing. Researchers found two-sided significant results = 0.000 < α 0.05. Therefore, the researcher concluded that the use of the Berlitz method had a significant impact on student's vocabulary mastery at SMP Berdikari Cijaku Lebak-Banten.